Admen, mad men and the real world of advertising essential lessons for business and life - Marinaccio, Dave. (New York Arcade Publishing, 2015)
In this entertaining new book, he takes us inside the world of advertising, offering stories and observations from working at America's best-known agencies with clients from Pizza Hut to the Holocaust Museum.

In short chapters leavened with wit, Dave pulls back the curtain and shares his insights on how marketing decisions are made and other lessons. Hist topics range from logos, the big idea, and selling perfume to do-overs, celebrities, meetings-manship, and how we undervalue our gifts. And more than a few lessons turn out to be apt not just for business but also for our stressed-out lives.

Easily digestible by interns, CEOs, or anyone who has ever watched a television commercial or clicked on a banner ad, this book is a must for anyone who lives, works, or plays in today's commercial culture.
Includes index.
Donated by Prof. Michelle Roxas
Keywords: Advertising; Marketing; Advertising executives -- Biography